Pengaruh Harga Paket dan Kualitas Jaringan Terhadap Keputusan Pembelian Kartu Prabayar Xl di Aceh Barat - Armi Armi (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the effect of package price and network quality on the purchasing decision of XL prepaid cards in West Aceh Regency, both partially and simultaneously. The research employs a quantitative approach with a descriptive research design. The population includes all users of XL prepaid cards in West Aceh, with an undetermined total number. The sample was determined using a purposive sampling technique based on Cochran’s formula, resulting in 96 respondents. Primary data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS software.The findings indicate that the package price variable (X₁) has a significant effect on the purchasing decision of XL prepaid cards in West Aceh, with a significance value of 0.000 < 0.05 and a positive coefficient. This suggests that the more affordable and competitive the package price, the higher the consumers’ purchasing decisions. Meanwhile, the network quality variable (X₂) does not have a significant effect on purchasing decisions, with a significance value of 0.410 > 0.05. However, both variables simultaneously have a significant effect on purchasing decisions, as shown by the F-test significance value of 0.000 < 0.05. The coefficient of determination (R²) of 0.642 indicates that 64.2% of the variation in purchasing decisions can be explained by package price and network quality, while the remaining 35.8% is influenced by other factors not examined in this study.Therefore, it can be concluded that package price is the most dominant factor influencing the purchasing decision of XL prepaid cards in West Aceh, while network quality has not yet become a primary consideration for consumers.